Sustainable Tourism Planning in The Kingdom of Saudi Arabia - Hassan, Ashraf Fawzy (Journal of engineering sciences and information technology, 2025)
This study aims to analyze the integration of sustainable tourism principles into resort planning in the Kingdom of Saudi Arabia, focusing on the environmental and social challenges arising from the rapid growth of the tourism sector. A qualitative case study approach was adopted, involving the analysis of national strategy documents and semi-structured interviews with tourism experts and planners. The findings indicate that the application of sustainability principles remains inconsistent, with key challenges including weak institutional coordination and limited community participation in planning processes. The study demonstrates that early integration of sustainability enhances the long-term success and effectiveness of tourism projects. It recommends strengthening collaboration among stakeholders, developing clear regulatory frameworks to support sustainable tourism standards, investing in digital infrastructure, and training human resources. These results contribute to achieving the goals of Saudi Vision 2030 by balancing economic development with the preservation of environmental and social resources.